2019
DOI: 10.1111/jace.16965
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing TiO2 amorphous precursors for polymorph selection: An in situ TEM study of phase formation and kinetics

Abstract: Selective synthesis of metastable polymorphs requires a fundamental understanding of the complex energy landscapes in which these phases form. Recently, the development of in situ high temperature and controlled atmosphere transmission electron microscopy has enabled the direct observation of nucleation, growth, and phase transformations with near atomic resolution. In this work, we directly observe the crystallization behavior of amorphous TiO 2 thin films grown under different pulsed laser deposition conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Recent X-ray diffraction and electron microscopy studies of the thermally induced transition of amorphous pulsed laser deposition (PLD) TiO 2 films to either anatase or brookite crystal forms suggest that there is considerable tensile strain intrinsic to as-deposited amorphous oxide films arising from constrained Ti–O bonding environments, oxygen deficiencies, and the activation energies that must be surmounted to fully relax local microstructures. This strain provides an internal driving force for nucleation and crystallization of the oxide as annealing temperatures are raised, dependent upon initial deposition conditions, including O 2 partial pressure. , Similar X-ray diffraction studies have tracked the conversion from amorphous to crystalline TiO 2 thin films . Most interestingly, Klein and co-workers have recently demonstrated that SG TiO 2 layers deposited on certain FTO surfaces experience a kind of “templating” of the oxide to FTO grains, with thin oxide films resulting which are mixtures of anatase and rutile forms of TiO 2 …”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Recent X-ray diffraction and electron microscopy studies of the thermally induced transition of amorphous pulsed laser deposition (PLD) TiO 2 films to either anatase or brookite crystal forms suggest that there is considerable tensile strain intrinsic to as-deposited amorphous oxide films arising from constrained Ti–O bonding environments, oxygen deficiencies, and the activation energies that must be surmounted to fully relax local microstructures. This strain provides an internal driving force for nucleation and crystallization of the oxide as annealing temperatures are raised, dependent upon initial deposition conditions, including O 2 partial pressure. , Similar X-ray diffraction studies have tracked the conversion from amorphous to crystalline TiO 2 thin films . Most interestingly, Klein and co-workers have recently demonstrated that SG TiO 2 layers deposited on certain FTO surfaces experience a kind of “templating” of the oxide to FTO grains, with thin oxide films resulting which are mixtures of anatase and rutile forms of TiO 2 …”
Section: Introductionmentioning
confidence: 90%
“…This strain provides an internal driving force for nucleation and crystallization of the oxide as annealing temperatures are raised, dependent upon initial deposition conditions, including O 2 partial pressure. 2,49 Similar X-ray diffraction studies have tracked the conversion from amorphous to crystalline TiO 2 thin films. 50 Most interestingly, Klein and co-workers have recently demonstrated that SG TiO 2 layers deposited on certain FTO surfaces experience a kind of "templating" of the oxide to FTO grains, with thin oxide films resulting which are mixtures of anatase and rutile forms of TiO 2 .…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…So how does changing the deposited structure change which phases could be stabilized? There is well-established precedent for the influence of precursor structure on the morphology and crystallographic texture of the ground-state phase in biology, geology, and materials science. For example, it has been shown in some transition-metal oxides that varying the deposition rate leads to the formation of different polymorphs, presumably due to changes in the local structure prior to crystallization. Metastable phases have been stabilized by engineering the entropy or enthalpy of alloyed systems, but this route is not viable for less-complex chemistries. , Perhaps a metastable phase could be stabilized if the temperature is low enough or quenched quickly enough, so that the as-deposited structure could have remnant metastability, similar to what has been done in the shuttered layer-by-layer growth of Ruddlesden–Popper phases. But when the temperature is high enough to induce diffusion in similar compounds as well as absorption-controlled growth, as in the present work (where the substrate temperature was kept above 750 °C), remnant capture cannot entirely account for the difference in phase formation pathways.…”
Section: Introductionmentioning
confidence: 99%